IDENTIFIKASI KEMAMPUAN LITERASI DIGITAL MAHASISWA PENDIDIKAN KIMIA PADA PEMBELAJARAN DARING - Fatimatuzzahro Nurazizah; Dedi Irwandi; Evi Sapinatul Bahriah (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2026)
The implementation of online learning as a form of adaptation to the digital era requires students to have good digital literacy skills so that learning activities can run productively, effectively, and efficiently. This study aims to determine the level of digital literacy of Chemistry Education students in online learning using Microsoft Teams. The research method used is quantitative descriptive with instruments in the form of a digital literacy questionnaire and interviews. The research sample was determined using purposive sampling technique with a total of 181 students. Data analysis was carried out using descriptive statistics. The results showed that the digital literacy skills of Chemistry Education students were in the “good” category with an average score of 79.96%. The technical dimension scored 80.06%, the cognitive dimension 79.24%, and the socio-emotional dimension 79.63%. The highest indikators included operational skills in using technological devices and Microsoft Teams, understanding digital ethics and copyright, and applying netiquette and data security protection. However, continuous strengthening of digital literacy is still needed to achieve an overall excellent category. Thus, it can be concluded that the digital literacy skills of Chemistry Education students are in the “good” category.